ABCC4/MRP4: a MYCN-regulated transporter and potential therapeutic target in neuroblastoma - Huynh, Tony; Norris, Murray D.; Haber, Michelle; Henderson, Michelle J. (Frontiers in Oncology, 2012)
Resistance to cytotoxic drugs is thought to be a major cause of treatment failure in childhood neuroblastoma, and members of the ATP-binding cassette (ABC) transporter superfamily may contribute to this phenomenon by active efflux of chemotherapeutic agents from cancer cells. As a member of the C subfamily of ABC transporters, multidrug resistance-associated protein MRP4/ABCC4 has the ability to export a variety of endogenous and exogenous substances across the plasma membrane. In light of its capacity for chemotherapeutic drug efflux, MRP4 has been studied in the context of drug resistance in a number of cancer cell types. However, MRP4 also influences cancer cell biology independently of chemotherapeutic drug exposure, which highlights the potential importance of endogenous MRP4 substrates in cancer biology. Furthermore, MRP4 is a direct transcriptional target of Myc family oncoproteins and expression of this transporter is a powerful independent predictor of clinical outcome in neuroblastoma. Together, these features suggest that inhibition of MRP4 may be an attractive therapeutic approach for neuroblastoma and other cancers that rely on MRP4. In this respect, existing options for MRP4 inhibition are relatively non-selective and thus development of more specific anti-MRP4 compounds should be a major focus of future work in this area.